2011
DOI: 10.1007/s11248-011-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of insect-resistant transgenic cotton with chimeric TVip3A* accumulating in chloroplasts

Abstract: An optimized vip3A gene, designated as vip3A* was chemically synthesized and a thi1 gene chloroplast transit peptide coding sequence was attached to its 5' end to produce the tvip3A*. vip3A* and tvip3A* genes were transformed into Gossypium hirsutum cv. Zhongmiansuo35. Of 42 independent transformants, 36 were positive for the vip3A* or tvip3A* gene. Four independent transgenic T1 lines with single-copy insertions and unchanged phenotypes (CTV1 and CTV2 for tvip3A*, and CV1 and CV2 for vip3A*) were selected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Cotton has also been transformed with a synthetic vip3A gene fused to a chloroplast transit peptide coding sequence (119). The Vip3A protein accumulated in chloroplasts, and its concentration in plants was higher than that in plants transformed with just the synthetic gene.…”
Section: Expression In Plantsmentioning
confidence: 99%
“…Cotton has also been transformed with a synthetic vip3A gene fused to a chloroplast transit peptide coding sequence (119). The Vip3A protein accumulated in chloroplasts, and its concentration in plants was higher than that in plants transformed with just the synthetic gene.…”
Section: Expression In Plantsmentioning
confidence: 99%
“…The function of THI1 signal peptide in cotton is consistent with that reported in Arabidopsis [57], who demonstrated that the transit signal peptide of THI1 protein could transfer the GFP protein into chloroplasts. In addition, we previously reported that Vip3A, a Bacillus thuringiensis toxin protein, was transferred into the chloroplasts of cotton by the transit signal peptide of Arabidopsis THI1 protein [58].…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative insecticidal protein (Vip3Aa) from Bacillus thuringiensis (Bt) is a candidate novel toxin because of its greater toxicity and unique receptor binding sites (Tabashnik et al, 2008 ). Cry1Ac is produced during the bacterial reproductive growth phase, while Vip3Aa is secreted during the bacterial vegetative growth phase (Wu et al, 2011 ). Both are non-homologous insecticidal proteins possessing different receptors within the midgut of Lepidoptera with unique insecticidal impact (Yu et al, 1997 ; Lee et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, fusion protein was used in cotton plants to increase the concentration of Vip3A protein by producing chimeric Tvip3A * protein. Transgenic plants possessing Tvip3A * genes showed an approximately 100% mortality rate in case of beet armyworm and FAW (Wu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%